Decreased Hemoglobin Concentration and Iron Metabolism Disorder in Periodontitis: Systematic Review and Meta-Analysis - Wu, Donglei; Lin, Zhengshen; Zhang, Shiwei; Cao, Fengdi; Liang, Defeng; Zhou, Xincai (Frontiers in Physiology, 2020)
Background:Periodontitis is a chronic inflammatory disease with possible infectious component. Anemia of inflammation (AI) occurring in various chronic diseases alters the hemoglobin (Hb) concentration and iron status. Currently, the association between periodontitis and AI is still in controversy. The aim of this study was to assess the alterations of the level of hematological parameters and iron metabolism markers in patients with or without periodontitis. Methods: Electronic databases (MEDLINE, EMBASE, and Cochrane) were searched to identify publications about anemia and periodontitis. Subgroup analysis regarding gender, extent of periodontitis, and sample size were performed using STATA 12.1. Results: Sixteen studies were included in this meta-analysis. Pooled results showed a decrease in Hb (SMD= -0.76, 95%CI= (-1.15, -0.37)), RBC (SMD= -0.69, 95%CI= (-1.09, -0.29)), HCT (SMD=-1.13, 95%CI= (-1.69, -0.57)), MCV(SMD=-0.16, 95%CI= (-0.32 -0.01)), and MCH (SMD=-0.16, 95%CI= (-0.28, -0.04)), but upregulation in ESR (SMD=0.63, 95%CI= (0.06, 1.19)). Additionally, patients with periodontitis had a higher level of hepcidin (SMD= 0.59, CI = (0.05, 1.12) and decreased level of transferrin (SMD=-4.6, CI = (-13.1, -3.90)), with high heterogeneity. Conclusion: This meta-analysis indicates that periodontitis decreases hemoglobin concentration and disturbs the balance of iron metabolism, which confirms strength of association between periodontitis and the development tendency of AI, especially for severe periodontitis. More unbiased cohort studies with larger sample sizes are still warranted to make a definitive judgment in the future.